Analysis Flies Density at Final Waste Disposal Jember Distric Area, Indonesia (Studi at Pakusari landfill and Ambulu landfill) - Anita Dewi Moelyaningrum; Disny Prajnawita; Prehatin Trirahayu Ningrum (Universitas Airlangga, 2020)
Introduction: Flies can transmitted disease. The final waste disposals were the breeding place of flies, especially when the final waste disposals weren`t implementation in good management. The objectives of the research were to analyze the differences between flies density in the Pakusari landfill and Ambulu landfill, Jember District, Indonesia. Method: the method was analytic with a cross-sectional design. The data were collected with observation, interview and measure the flies density. The population was all of the area kavling in the Pakusari and Ambulu landfill. The samples were total population. There were 4 active kavling in the landfill, and interview 68 head of the family which stays around the landfill how the flies disrupt their daily activity. The measurements of flies density were using fly grill, stopwatch, form the flies density. The type of flies was identification. Result and Discussion: Waste disposal management at Pakusari landfill was a controlled landfill, and Ambulu was open dumping. Both of flies density of the landfill were categorized very high. The measurement of flies density was in September 2019, whereas the Pakusari landfill using open dumping because of the equipment was broken. The highest flies density on Pakusari at kavling 2 dan 3,4 were 44,4 per 30 seconds (point 1) and 42,4 per 30 seconds (point 1). At kavling 2, 3 Ambulu landfills were 34 per 30 seconds (point 6) and 31,4 per second (point 1) There were sig difference flies density between Pakusari and Ambulu landfill (p=0,000). The most of flies were Musca Domestica(81%). The most distribution of flies were disturbed by the view, causing diarrhea, typus. Conclussion: Waste disposal landfill management should be improving with sanitary landill to control the flies density and decrease the vector-borne disease.